OUT-OF SCHOOL & NON-FORMAL EDUCATION: UKRAINIAN AND EUROPEAN DIMENSIONS - Olena Lytovchenko (National Academy of Educational Sciences of Ukraine, 2020)
Out-of-school education in Ukraine has its own traditions and experience, at the same time, develops in the context of European trends, adopts the best foreign practices, in particular, institutions and organizations of non-formal education in European countries. Out-of-school education in Ukraine and non-formal education in European countries have significant differences, but similar goals and values. The purpose of the paper is to present the results of the study of common goals and values of out-of-school education in Ukraine and nonformal education in European countries, as well as to analyze the regulatory aspects, practical experience. According to the results of the analysis, the common goals and values of out-ofschool education in Ukraine and non-formal education in European countries include: providing children and youth with opportunities for non-formal and informal learning, creating conditions for leadership, communication, language learning, teamwork, social roles, development of critical thinking, self-awareness and awareness of others, responsibility; socialization, creative realization and professional self-determination of children and youth as well as promoting active citizenship, supporting youth activities.